Synthesis and Characterization of Nano-Hydroxyapatite Obtained from Eggshell via the Hydrothermal Process and the Precipitation Method - Shih-Ching Wu; Hsueh-Chuan Hsu; Hsueh-Fang Wang; Shu-Ping Liou; Wen-Fu Ho (Molecules, 2023)
Hydroxyapatite (HA) is a major component of the inorganic minerals in the hard tissues of humans and has been widely used as a biomedical ceramic material in orthopedic and dentistry applications. Because human bone contains several impurities, including carbonates, chlorides, fluorides, magnesium, and strontium, human bone minerals differ from stoichiometric HA. Additionally, natural bone is composed of nano-sized HA, and the nanoscale particles exhibit a high level of biological activity. In this paper, HA is prepared via the hydrothermal process because its reaction conditions are easy to control and it has been shown to be quite feasible for large-scale production. Therefore, the hydrothermal process is an effective and convenient method for the preparation of HA. Furthermore, eggshell is adopted as a source of calcium, and mulberry leaf extract is selectively added to synthesize HA. The eggshell accounts for 11% of the total weight of a whole egg, and it consists of calcium carbonate, calcium phosphate, magnesium carbonate, and organic matter. Eggshell contains a variety of trace elements, such as magnesium and strontium, making the composition of the synthesized HA similar to that of the human skeleton. These trace elements exert considerable benefits for bone growth. Moreover, the use of eggshell as a raw material can permit the recycling of biowaste and a reduction in process costs. The purpose of this study is to prepare HA powder via the hydrothermal method and to explore the effects of hydrothermal conditions on the structure and properties of the synthesized HA. The room-temperature precipitation method is used for the control group. Furthermore, the results of an immersion test in simulated body fluid confirm that the as-prepared HA exhibits good apatite-forming bioactivity, which is an essential requirement for artificial materials to bond to living bones in the living body and promote bone regeneration. In particular, it is confirmed that the HA synthesized with the addition of the mulberry leaf extract exhibits good in vitro biocompatibility. The morphology, crystallite size, and composition of the carbonated nano-HA obtained herein are similar to those of natural bones. The carbonated nano-HA appears to be an excellent material for bioresorbable bone substitutes or drug delivery. Therefore, the nano-HA powder prepared in this study has great potential in biomedical applications.